EFFECTIVENESS OF FINGER GRIP RELAXATION TECHNIQUE ON PAIN IN POST SECTIO CAESAREA : A LITERATURE REVIEW - Sukmawati, Sukmawati; Nurhakim, Furkon; Mamuroh, Lilis (Universitas Aisyah Pringsewu, 2023)
Sectio Caesarea is an act of opening the abdominal wall and uterine wall to give birth to the fetus. This process causes pain from the surgical incision. Finger grip relaxation therapy is an alternative to reduce post-Sectio Caesarea pain. The purpose of this literature study is to determine the effectiveness of finger-held relaxation therapy for pain in post-sectio caesarea patients.The literature study method uses a narrative review with a quantitative descriptive approach. Article searches used the Garuda, PubMed and ScienceDirect databases, with inclusion criteria: research published in 2018-2022, using Indonesian and English, original research, and full text available. Screening results based on keywords and inclusion criteria obtained nine articles for further analysis. Of the 9 articles analyzed, all stated that finger grip relaxation can reduce pain intensity in post-cesarean section patients. Fingers grip relaxation is expected to be use as an alternative to reduce pain intensity in post section caesaria patients.